Race to the bottom of the sea - Eagar, Lindsay (Candlewick Press, 2017)
"When her parents, the great marine scientists Dr. and Dr. Quail, are killed in a tragic accident, eleven year old Fidelia Quail is racked by grief. But she is forced out of her mourning when she's kidnapped by Merrick the Monstrous, a pirate whose list of crimes stretches longer than a ribbon eel. Her task? Use her marine know-how to retrieve his treasure, lost on the ocean floor. As Fidelia and the pirates close in on the prize, with the navy hot on their heels, she realizes that Merrick doesn't expect to live long enough to enjoy his loot. Could something other than black-hearted greed be driving him? Will Fidelia be able to master the perils of the ocean without her parents - and piece together the mystery of Merrick the Monstrous before it's too late?"--Provided by OCLC.